Laughter Interventions to Improve Psychological Well-Being/QoL in Cancer Patients: A Mini Systematic Review - Anastasia Olympiou; Sana Ahmed (SAGE Open)
Literature suggests that laughter interventions can positively influence psychological well-being and quality of life (QoL) in various populations, yet their efficacy among cancer patients remains underexplored. This mini systematic review aims to examine the cross-sectional associations between laughter/humor interventions and psychological wellbeing/Quality of life and synthesize the latest quantitative evidence regarding the effects of laughter interventions on the psychological wellbeing/Quality of life of cancer patients as well as the longitudinal relationships between interventions and outcome. A comprehensive search was conducted across electronic databases to identify relevant studies published from 2011 until 2022. Eligible studies were those examining the impact of laughter interventions on psychological well-being and Quality of Life in cancer patients. Five studies met the inclusion criteria and were included in the review. The findings indicate significant improvements in various psychological parameters following laughter interventions among cancer patients, including stress, depression, anxiety, overall Health Related Quality of Life (HRQoL), emotional well-being, Global Health Status & QoL, mental well-being, and positive mood. Moreover, the review highlights the synergistic effects of laughter when combined with other therapeutic elements. However, it was noted that laughter therapy did not demonstrate significant efficacy for moderate to severe depression among cancer patients. Longitudinal effects of laughter interventions on psychological well-being and QoL remain inconclusive. This systematic review underscores the beneficial effects of laughter interventions on the psychological well-being and QoL of cancer patients. It suggests the potential for multidisciplinary approaches, led by Health Psychology Practitioners, to develop and implement tailored laughter therapy programs for this population. Further research is warranted to elucidate the longitudinal effects and optimal delivery methods of laughter interventions in the context of cancer care.